Hubungan di Antara Kepimpinan Autentik dan Tingkah Laku Kerja Inovatif Pekerja dalam Sektor Perkhidmatan - Marinah Musa; Eta Wahab (Research in Management of Technology and Business, 2024)
The innovative work behavior of individuals in the workplace is crucial for every high performance organization. Authentic leadership play a key role in improve individual innovative behavior among worker. However, there is still a lack of study done in this area especially for the perspective of service sector in Malaysia. Thus, the purpose of this research is to find the relationship between authentic leadership and innovative work behavior in the service sector. This study is a quantitative study where a survey form had been distributed to respondents who are employees of fast food companiesin the service sector in Batu Pahat. Atotal of 132 questionnaires had been distributed to fast food workers in the service sector with a response rate of 78%. Data has been analyzed using Statistical Package for The Social Science (SPSS). Descriptive methods and correlation analysis had used. This study found that there is a relationship between authentic leadership and innovative work behavior among employee in service sector.